2015
DOI: 10.3389/fonc.2015.00256
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Tumor Control and Normal Tissue Complication Probabilities in Advanced Head-and-Neck Cancer for Dose-Escalated Intensity-Modulated Photon and Proton Therapy

Abstract: IntroductionPresently used radiochemotherapy regimens result in moderate local control rates for patients with advanced head-and-neck squamous cell carcinoma (HNSCC). Dose escalation (DE) may be an option to improve patient outcome, but may also increase the risk of toxicities in healthy tissue. The presented treatment planning study evaluated the feasibility of two DE levels for advanced HNSCC patients, planned with either intensity-modulated photon therapy (IMXT) or proton therapy (IMPT).Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
2
9
0
1
Order By: Relevance
“…82 Additional NTCP models are being investigated to estimate the efficacy of IMPT for specific HNCs sub-sites or when IMPT is delivered in a mixed modality treatment. 8386…”
Section: Future Directionsmentioning
confidence: 99%
“…82 Additional NTCP models are being investigated to estimate the efficacy of IMPT for specific HNCs sub-sites or when IMPT is delivered in a mixed modality treatment. 8386…”
Section: Future Directionsmentioning
confidence: 99%
“…Conformal dose distributions are typically provided by advanced photon therapy techniques like intensity‐modulated radiotherapy (IMRT) 1. While intensity‐modulated proton therapy (IMPT) can more effectively reduce the dose to healthy tissue2, 3, 4, 5 and thus allow for further dose escalation,6 proton beams are prone to range uncertainties if the penetrated tissue changes during therapy. Gradual intratherapy changes in HNC patient anatomy, mainly caused by weight loss, shrinkage of tumor, and shift of close‐by structures can be assessed via imaging, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate and evaluate the effectiveness of PBT over photon therapy, several studies using the NTCP modeling analysis exist. Jakobi et al conducted in silico study using NTCP modeling analysis in head and neck region to identify patients who may benefit from PBT [31][32][33]. Makishima et al showed that NTCP value for the lung and heart decreased in proton plan compared with photon plan in esophageal cancer [34].…”
Section: Discussionmentioning
confidence: 99%